2005
DOI: 10.1091/mbc.e05-04-0345
|View full text |Cite
|
Sign up to set email alerts
|

The Retrotranslocation Protein Derlin-1 Binds Peptide:N-Glycanase to the Endoplasmic Reticulum

Abstract: The deglycosylating enzyme, peptide:N-glycanase, acts on misfolded N-linked glycoproteins dislocated from the endoplasmic reticulum (ER) to the cytosol. Deglycosylation has been demonstrated to occur at the ER membrane and in the cytosol. However, the mechanism of PNGase association with the ER membrane was unclear, because PNGase lacked the necessary signal to facilitate its incorporation in the ER membrane, nor was it known to bind to an integral ER protein.Using HeLa cells, we have identified a membrane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…In addition, other cytosolic ERAD components are also recruited to the ER by the multiprotein complex. For examples, both Derlin-1 and p97/ VCP interact with the peptide:N-glycanase, a key enzyme that removes N-glycan from misfolded ER proteins before proteasomal degradation (39,40). Peptide:N-glycanase also interacts with hHR23B, a polyubiquitin-binding protein that chaperones polyubiquitinated ERAD substrates to the proteasomes for degradation (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other cytosolic ERAD components are also recruited to the ER by the multiprotein complex. For examples, both Derlin-1 and p97/ VCP interact with the peptide:N-glycanase, a key enzyme that removes N-glycan from misfolded ER proteins before proteasomal degradation (39,40). Peptide:N-glycanase also interacts with hHR23B, a polyubiquitin-binding protein that chaperones polyubiquitinated ERAD substrates to the proteasomes for degradation (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of a proteasome inhibitor in the experiment led to an accumulation of the deglycosylated forms of substrates (Fig. 5, D and E, compare lanes 7 and 5), whose N-linked glycans are removed by a cytosolic N-glycanase attached to Derlin-1 (17). Knockdown of SelK in MG132-treated cells did not affect clearance of the HA-tagged NHK (Fig.…”
Section: Isolation and Identification Of Proteins Associated With Selk-mentioning
confidence: 90%
“…First, these proteins are involved in or are required for degradation of many ERAD substrates (8 -14). Second, Derlin-1 and -2 were found to interact with lumenal (8,11), membrane (15,16) and cytosolic (9,14,17) proteins required for retrotranslocation. Finally, Derlins are capable of forming homo-and heterooligomers (11,15,16,18), which is consistent with their ability to form large complexes and serve as channels.…”
mentioning
confidence: 99%
“…Further- more, mammalian PNGase forms protein complexes via its N-terminal peptide:N-glycanase/UBA or UBX-containing protein (PUB) domain with other molecules playing central roles in ERAD such as p97/Cdc48/VCP (cytosolic AAA ATPase), Derlin-1 (putative retrotranslocation channel), and AMFR (ER-associated ubiquitin ligase E3). This demonstrates that PNGase is profoundly involved in ERAD as a deglycosylating enzyme for substrate proteins (21,22).…”
Section: B the 3 Pathways For The Formation Of Fossmentioning
confidence: 90%
“…The generation of FOSs was directly linked to ERAD because the cytoplasmic product of the PNGase gene ( png1) from yeast S. cerevisiae is known to interact with the 20S proteasome. Many subsequent reports of ERAD-related protein interactions have revealed that PNGase, a FOSproducing enzyme, is a major component of the ERAD pathway (19)(20)(21)(22).…”
Section: B the 3 Pathways For The Formation Of Fossmentioning
confidence: 99%